Production of effervescent tablets of rosela flower (Hibiscus sabdariffa L.) and its effect on the in vivo immune system - Arti Hastuti; Mardiah; Lucianawati Dewi Dewi; Lia Amalia; Dwi Aryanti Nur’utami; Tiana Fitrilia (UHAMKA PRESS, 2023)
Rosella effervescent tablet is an effervescent product in the form of tablet made from roselle petal extract. This study aimed to evaluate the antioxidant content of the resulting effervescent tablets and the effect of effervescent tablets on the in vivo immune system. The technique for making effervescent tablets used the wet granulation method. Immune system analysis used rat test animals. The type of rat is Sprague Dawley. There were three treatment groups, each group consisted of 5 rats. The first group was the standard group, group 2 was the positive control group which was given Stimuno Forte at a dose of 1.35 mg/kg BW, and the treatment group 3 was given roselle effervescent tablets at a dose of 8.1 mg/kg BW by sonde for 28 days. Blood sampling (leukocytes, differential leukocytes, lymphoid organs (spleen and liver), total serum protein, and serum albumin) was performed on day 0 and day 29. The chemical test results of the effervescent tablets showed an IC50 of 10.35 ppm, a vitamin C content of 2.28 mg/tablet, and an anthocyanin content of 22.12 mg/L. The results of the research on rosella effervescent tablets at a dose of 8.1 mg/kg BW provided a protective effect on the immune system of rat with an average parameter of leukocyte count of 7.58×103/µL, total serum protein of 10.25 g/dl, and relative liver weight of 3. 11% and still within the normal range of Sprague Dawley rats.